Condutividade elétrica da solução sólida céria-zircônia dopada com ítrio e gadolínio - Antunes, Fábio Coutinho (2009)
Rare earth doped ceria has a great potential to be used as electrolyte in temperatures around 800 °C in fuel cells due to its higher electrical conductivity than YSZ. However, the reduction of Ce+4 to Ce+3 in low oxygen partial pressure has introduced limitations for using doped ceria electrolyte due to electronic conduction. Among the several ceria solid solutions, CeO2-ZrO2-Y2O3 attracts attention because its stability at temperatures around 800 °C and oxygen partial pressures up 10-18 atm. On the other hand, ceria solid solutions are very sensitive to the purity of the raw material. For these reason, it is common to find secondary phase along the grain boundary blocking the electrical conduction. For these electrolytes, impurities control the grain boundary conductivity. In this work, powders (Ce0,9-xYx)Zr0,1 and (Ce0,9-xGdx)Zr0,1 with 0.10 ≤ x ≤ 0.24 were prepared by oxides mixing. The effect of successive calcinations and the addition La2O3 was evaluated. Samples obtained by isostatic pressing, were sintered between 1450 and 1600 ° C with two hours of soaking time. Sintered samples were characterized by density measurements, X rays diffraction, scanning electron microscopy and impedance spectroscopy. Among all samples, those doped with 12 mol% of co-dopant aliovalente (Y2O3 ou Gd2O3) showed similar electrical behavior. For these samples it was observed a large increase of grain boundary electrical conductivity for calcined compositions and doped with La2O3 resulting a total electrical conductivity of 4,4x10-4 S.cm-1 at 450 °C in the same order of magnitude of electrolytes Z8Y prepared for this work. Compositions containing Y+3 and La2O3 showed higher electrolytic domain compared to the other investigated compositions.